ANALISIS PENETAPAN HARGA POKOK PRODUKSI KOPI KURMA DI CAFE OEN KOPI KOTA BANDA ACEH - Fuqara, Fantashir Awwal; Tanjung, Yulia Windi (STAI Darul Qalam Tangerang, 2024)
The study aims to analyze the cost of goods produced at Oen Kopi Cafe Banda Aceh City. This research method is descriptive quantitative. Primary data in this study is production cost data. The data was analyzed using the Cost Plus Pricing method in the Full Costing approach. The results of the study were obtained the selling price of beverage products Kopi Kurma set by Oen Kopi Cafe was 23.000 rupiah, according to the Full Costing approach is 17.019,88 rupiah, thus obtaining a difference of 5.980 rupiah. Thus, the selling price of products in one production set by Oen Kopi Cafe is greater when compared to the costs calculated using the cost of goods produced with the Full Costing method approach. So Oen Kopi Cafe gets significant benefits.